Mammary analog secretory carcinoma parotid gland: Case report of a recently described tumor with review of literature - Vandana L. Gaopande; Maithili M. Kulkarni; Siddhi G. S. Khandeparkar; Avinash R. Joshi (Asian Journal of Oncology, 2017)
Mammary analog secretory carcinoma (MASC) is a low-grade malignant tumor of salivary glands. It is so named because of its cytohistopahological, immunohistological, and cytogenetic resemblance to secretory carcinoma of the breast. Since the first description of this tumor in 2010, about 70 cases have been reported in literature. We report a case of this recently described tumor in a 21-year-old female. The radiological diagnosis of her parotid swelling was pleomorphic adenoma. The cytological evaluation was suggestive of oncocytoma. The histopathology showed a low-grade malignant neoplasm and the differential included papillary variant of acinic cell carcinoma, oncocytic variant of mucoepidermoid carcinoma, and MASC. Immunohistochemistry confirmed the diagnosis of MASC. We have included a brief review of literature.